PENGAWASAN PEMERINTAH DAERAH TERHADAP PELAKSANAAN PERLINDUNGAN TENAGA KERJA INDONESIA DI KABUPATEN BREBES - Amalia, Rizka Nur; Lestari, Hesti (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2017)
This research is based on fact that Implementation of Indonesian labor protection is still notoptimum as there is a labor of Indonesia in Brebes Regency who cannot return to areas of origin, suffered acts of violence and the wages are not paid. The purpose of this research is to know the influence of the Controlling of local governments to the implementation of Indonesia Labor Protection in Social Service, Labor and transmigration Brebes Regency. This research methodology uses a quantitative approach. The sample in this research amount 27 respondents randomly. Method of collecting data by using the questionnaire given to the entire sample in this research. The research questionnaire using likert scale type and through the stages of test validity, reability, cross-tabulations, correlation rank kendall, analysis of correlation coefficient determination test, and kendall Concordance test as a method of data processing research.Based on The results of research showed that, there is influences between controlling of local government on the implementation of Indonesian Labor Protection where the results of the calculation of correlation rank kendall tau shows Z-count (2.97) Ëƒ Z tables (1.96). Based on this research, Controlling influential to the implementation of labor protection in Social Service, Labor and transmigration Brebes Regency. Those results proved by a test of of the coeffisien of determination (KD) shows that Controlling influential of 19.27% to the implementation of Indonesian labor protection. The recommendations given by the author that should be improved communication between employees and PPTKIS to reduce misinformation that Indonesian Labor who are abroadand need for education and training related to the Procedure of Placement and Protection of Indonesian Labor for employees and PPTKIS.